2020
DOI: 10.1055/s-0040-1708863
|View full text |Cite
|
Sign up to set email alerts
|

Cost Implications of Varying the Surgical Setting and Anesthesia Type for De Quervain Release Surgery

Abstract: Background First extensor compartment release is a common surgical procedure that represents a financial burden to the health care system. Questions/Purposes Study questions included (1) whether surgical encounter costs differ based upon surgical setting (operating room [OR] vs. procedure room [PR]) or (2) based upon anesthesia choice (local only, Bier's block [BB], monitored anesthesia care [MAC], or general [GA]) for De Quervain release (DQR). Patients and Methods Consecutive adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Rates of pooled major medical complications were low and similar following oCTR performed in either setting, as were pooled surgical site/wound complications and iatrogenic complications. In light of these findings supporting a similar safety profile, prior studies illustrating a substantial cost reduction associated with use of the PR setting for oCTR when compared with the OR, [3][4][5][6][7][8][9][10][11][12][13] and similar clinical outcomes following oCTR performed in PR and OR settings, 33 we conclude that the value of utilizing the PR setting for oCTR is greater than that of the OR.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Rates of pooled major medical complications were low and similar following oCTR performed in either setting, as were pooled surgical site/wound complications and iatrogenic complications. In light of these findings supporting a similar safety profile, prior studies illustrating a substantial cost reduction associated with use of the PR setting for oCTR when compared with the OR, [3][4][5][6][7][8][9][10][11][12][13] and similar clinical outcomes following oCTR performed in PR and OR settings, 33 we conclude that the value of utilizing the PR setting for oCTR is greater than that of the OR.…”
Section: Discussionsupporting
confidence: 72%
“…Substantial literature within the field of hand surgery has suggested that one effective method of surgical cost reduction is the utilization of a procedure room setting (PR), rather than the operating room setting (OR) for minor procedures. [3][4][5][6][7][8][9][10][11][12][13] Compared with the more traditional OR surgical setting with full sterility utilizing regional or general anesthesia, office-based PR surgical settings for minor hand procedures use field sterility under pure local anesthesia with lidocaine and epinephrine. Generally, a tourniquet is not used in the PR setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the actual raw data of cost could not be disclosed because of contractual agreements at our institution, the impact of certain variables on cost can still be evaluated as a relative increase from a baseline value and has been used in other studies. 7 , 20 , 22 , 42 , 44 Lastly, this study was not designed as a cost-effectiveness analysis as we only evaluated surgical direct costs. Therefore, postoperative costs including those related to complications or time off of work were not considered, and the health state of each patient over time was not assessed.…”
Section: Discussionmentioning
confidence: 99%